Arista Wedding Project Innovation Strategy Design using Blue Ocean Strategy - Fitratillah Hilhanif (Universitas Ciputra Surabaya, 2023)
Arista Wedding Project is a family business that has officially established in October 2019, in the field of creative industry especially wedding organizer. Arista Wedding Project offers wedding services specializing in Islamic weddings and intimate weddings that prioritize professionalism, creativity, and youthfulness. The value of Arista Wedding Project is Impress Your Wedding Moment and provides education for marriage preparation. This study aims to find the Key Success Factor (KSF) through eliminate, reduce, raise and create process, to find the canvas strategy. This study also objected to find the right innovation strategy that can be applied to increase the usage of wedding planning and organizer in Arista Wedding Project by using Blue Ocean Strategy. The analysis used in this study are SWOT analysis, benchmark, KSF, six path frameworks, and ERRC Grid. The next step is to create a canvas strategy which will be compiled into an innovation strategy of Blue Ocean for Arista Wedding Project. The results of this study indicate that there are eleven KSF that need to be considered by Arista Wedding Project namely: service quality; type of service; human resource capabilities; price; marketing; portfolio; brand; vendor recommendations; service digitalization; and marriage preparation class. Based on these eleven factors, the innovation strategies that can be applied to Arista Wedding Project in accordance with the Blue Ocean Strategy are improving the capabilities of human resource, price differentiation, service digitalization through the website, and marriage preparation class.